2020
DOI: 10.1002/ccd.28975
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of cerebral oxygenation during rapid ventricular pacing and its impact on outcome in transfemoral transcatheter aortic valve implantation

Abstract: Background: Cerebral O 2 saturation (ScO 2) reflects cerebral perfusion and can be measured noninvasively by near-infrared spectroscopy (NIRS). Objectives: In this pilot study, we describe the dynamics of ScO 2 during TAVI in nonventilated patients and its impact on procedural outcome. Methods and Results: We measured ScO 2 of both frontal lobes continuously by NIRS in 50 consecutive analgo-sedated patients undergoing transfemoral TAVI (female 58%, mean age 80.8 years). Compared to baseline ScO 2 dropped signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Every episode of RVP increases the incidence of new atrial fibrillation, acute kidney injury, in-hospital mortality and 1-year mortality ( 21 ). In a 2021 study, the significant decrease of cerebral oxygenation observed during RVP was a predictor for the occurrence of neurological complications such as TIA/stroke and post-intervention delirium ( 115 ). The Chinese consensus on TAVR recognizes this danger by stating that “the total pacing time should be <15 s to avoid serious complications caused by prolonged hypoperfusion” ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Every episode of RVP increases the incidence of new atrial fibrillation, acute kidney injury, in-hospital mortality and 1-year mortality ( 21 ). In a 2021 study, the significant decrease of cerebral oxygenation observed during RVP was a predictor for the occurrence of neurological complications such as TIA/stroke and post-intervention delirium ( 115 ). The Chinese consensus on TAVR recognizes this danger by stating that “the total pacing time should be <15 s to avoid serious complications caused by prolonged hypoperfusion” ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable values of rSO 2 were observed pre- and post-operatively, but intraoperative desaturation was more substantial during the implantation of balloon-expandable devices, which is due to the implantation technique. More substantial desaturations during RVP were observed in patients with a higher EuroScore, who also showed an overall reduction in rSO 2 in our cohort [ 26 ]. Preoperative rSO 2 was lower in patients with a higher EuroScore who underwent on-pump cardiac surgery, and these patients were found to have increased postoperative mortality [ 18 , 41 ].…”
Section: Discussionmentioning
confidence: 77%
“…However, although significant, the actual numerical rise in rSO 2 was small in our cohort, and it must therefore be considered that confounding factors contributed to these slightly elevated rSO 2 values. To date, evidence on the course of cerebral NIRS following TAVI has focused mainly on the episode of RVP [ 25 , 26 , 27 ]. Consistent to the functionally circulatory arrest that is achieved during RVP, rSO 2 was seen to fall significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implantation of BEV requires rapid ventricular pacing for stabilization of the aortic root and accurate positioning of the prosthesis. Rapid ventricular pacing causes a state of low to no cardiac output resulting in cerebral hypoperfusion and may be associated with increased stroke risk [ 37 , 38 ]. Balloon post-dilatation is routinely applied with SEV and BEV to reduce paravalvular leak and has been described as predictor for acute cerebrovascular events [ 39 ].…”
Section: Discussionmentioning
confidence: 99%